1984
DOI: 10.1139/m84-049
|View full text |Cite
|
Sign up to set email alerts
|

Viable but nonrecoverable stage of Salmonella enteritidis in aquatic systems

Abstract: An environmental isolate (13- 1BB ) of Salmonella enteritidis serogroup C1 was inoculated into sterile Potomac River water microcosms to observe survival and culturability of the organism by employing acridine orange direct count, fluorescent antibody direct count, direct viable count, plate count on veal infusion agar and xylose lysine decarboxylase agar, and indirect enumeration by the most-probable-number method (MPN), using media selective for Salmonella. Loss of culturability on laboratory media was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
0
10

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(231 citation statements)
references
References 21 publications
8
213
0
10
Order By: Relevance
“…It may be inferred, therefore, that the unsupplemented albumen induces a quiescent state in salmonella. This phenomenon was noted by Rozak, Grimes and Colwell [23] who worked on water contaminated naturally with this organism. This novel proposal may be linked with the observation [24] that the alkalinity (pH 9-6) of the albumen induces a marked change in the characteristics, e.g.…”
Section: Discussionmentioning
confidence: 70%
“…It may be inferred, therefore, that the unsupplemented albumen induces a quiescent state in salmonella. This phenomenon was noted by Rozak, Grimes and Colwell [23] who worked on water contaminated naturally with this organism. This novel proposal may be linked with the observation [24] that the alkalinity (pH 9-6) of the albumen induces a marked change in the characteristics, e.g.…”
Section: Discussionmentioning
confidence: 70%
“…Escherichia coli O157:H Ϫ strain E 32511/HSC became nonculturable in sterilized distilled water microcosms at 4°C in about 21 days (24). Roszak et al reported that Salmonella serovar Enteritidis 13-1BB entered the nonculturable state within 48 h when it was incubated in Potomac River water (39). The clinical isolate Vibrio cholerae ATCC 14035 was found to enter the VBNC state in 6 to 9 days in Chesapeake Bay water at 4 to 6°C (51).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of nutrients, usually a small amount of yeast extract, is generally required (61). This direct viable count (DVC) method has been applied for detection of viable Vibrio vulnificus (91,105), estimation of viable counts of several gramnegative bacteria in an aquatic environment (15,20,28,29,112,115,127,128,129,150), and detection of viable bacteria in biofilms (151,152). In general, viable counts determined by the DVC method are considerably higher than the corresponding plate counts, which implies the existence of viable but nonculturable bacteria.…”
Section: Flow Cytometrymentioning
confidence: 99%